Expert judgment z-numbers as a ranking indicator for hierarchical fuzzy logic system - Rodzman S.B.B.; Ismail N.K.; Rahman N.A.; Aljunid S.A.; Nor Z.M.; Khalif K.M.N.K. (Institute of Advanced Engineering and Science, 2024)
Indexed by SCOPUS